Analysis of key flavor compounds in commercial cherry wines by HS-SPME-GC-MS, HS-GC-IMS, and sensory evaluation - Qi, Jiawei; Li, Jie; Liu, Zihan; Yang, Xuemei; Qi, Tingting; Wei, Guoqin; Yang, Juanxia; Liu, Cheng (Frontiers in Nutrition, 2025)
To investigate the characteristic flavor compounds and their differences in commercially available cherry wines, this study employed headspace solid-phase microextraction combined with gas chromatography–mass spectrometry (HS-SPME-GC-MS), headspace gas chromatography–ion mobility spectrometry (HS-GC-IMS), and sensory evaluation techniques to comprehensively analyze the volatile flavor compounds and sensory characteristics of 11 commercial cherry wines. The results showed that HS-SPME-GC-MS and HS-GC-IMS identified 74 and 49 volatile compounds, respectively. The combined use of both techniques detected a total of 101 compounds, identifying 15 additional key compounds compared to a single method, significantly improving the comprehensiveness of flavor characterization. Through odor activity value (OAV), relative odor activity value (ROAV), and variable importance in projection (VIP), 28 key flavor compounds were screened. Among them, esters (such as ethyl acetate, ethyl hexanoate, and ethyl octanoate) and alcohols (such as phenethyl alcohol) were the main contributors to the fruity and floral aroma of cherry wines, while benzaldehyde and 3-furfural were significantly associated with woody characteristics. Sensory evaluation indicated that sample C10 received the highest overall score, exhibiting prominent floral and fruity notes. Partial least squares regression (PLSR) analysis further confirmed that the floral and fruity attributes were strongly positively correlated with compounds such as linalool and α-terpineol, while the woody attribute was closely associated with benzaldehyde. Based on volatile compound fingerprinting and principal component analysis (PCA), samples C5, C9, and C10 exhibited similar flavor profiles with notable floral and fruity characteristics, whereas C11 displayed a unique woody character due to its high benzaldehyde content. This study provides a theoretical basis and data support for improving the flavor quality and differentiated quality control of cherry wine.